Acupuncture for cancer pain: a scoping review of systematic reviews and meta-analyses - Zhang, Yanji; Zhang, Yingrong; Liu, Suzhen; Li, Bocun; Song, Zhe; Han, Qi; Wang, Chang; Wang, Yiwei; Yu, Yanxin; Xia, Hongjie; Wang, Chun; Li, Jia (Frontiers in Oncology, 2023)
Background Due to the effectiveness and safety, acupuncture, one of the traditional therapies of Chinese medicine, has been widely used in clinical practice globally. A few systematic review or meta-analyses have proved its effectiveness and safety towards patients with cancer pain, while there are no syntheses among those evidence. The aim of this scoping review is to summarize the evidence from systematic reviews of acupuncture for the treatment of cancer pain and evaluate the breadth and methodological quality of these evidence as well. Methods The scoping review process was guided by the methodology framework of Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews (PRISMA ScR) and “Arkseyand O’Malley six-stage framework”. Electronic searches were carried out in several online databases from inception to Jan 2022. Systematic reviews and meta-analyses that involve any type of acupuncture for patients with cancer pain will be included. A pair of reviewers independently screened full texts. Moreover, review characteristics were extracted, and methodological quality was assessed using the AMSTAR 2 tool. Results Twenty-five systematic reviews and meta-analyses were included. Acupuncture is the most frequently included types of test group intervention (48%), followed by acupuncture + medicine (28%), and auricular acupuncture (12%). All the reviews have declared that acupuncture is an effective method for cancer pain treatment. Eleven reviews (44%) aiming at evaluating the safety also have confirmed that acupuncture is safe for treating cancer pain. However, most included studies were conducted in China. With certain geographical limitations, the findings were not representative within the region. The results of our review may owe to the synthesis of all kinds of cancer pain, and only 2 reviews described the type of cancer pain in detail. Conclusions This scoping review synthesizes and evaluates existing evidence of acupuncture for cancer pain. From this scoping review of systematic reviews and meta-analyses, there are clear recommendations for future studies: expanding the region of research in the world and trying to conduct the study of different types of cancer pain in details as much as possible. Evidences of acupuncture for cancer pain can inform clinical decision-making.